Studying yhe Effect of Nano Silver on Some Properties of Acrylonitrile Butadiene Styrene Copolymer for Medical Devices - Kareem Ahmed, Jaleel; Jabbar Braihi, Auda; Sattar Jabbar, Rami (International Journal of Engineering and Technology, 2018)
Antibacterial polymeric composites were prepared to manufacture medical devices and seats for hospitals. These composites prepared by adding nano silver (Ag NPs) by three ratios (3, 6, and 9 wt %) to Acrylonitrile butadiene styrene (ABS) terpolymer. The antibacterial activity was investigated against S. aureus and Salmoulla microorganisms using Agar well Diffusion method. Results showed that these composites have antibacterial ability against both S. aureus and Salmoulla microorganisms. At low Ag NPs concentration, the activity against Salmoulla is higher than that against S. aureus microorganism. But at higher concentrations, the activity against Salmoulla will be less than that against S. aureus microorganism. The mechanical properties improved due to the new interactions between nano silver and ABS matrix. Ag NPs addition reduces the surface wettability, enhances self-cleaning tendency, decreases the surface roughness and the groove continuity, enhances the surface bearing index, reduces both the core roughness depth and core fluid retention and shifted the thermal transitions towards low temperatures.
Keywords: .